Cerebrospinal fluid biomarkers of neurodegeneration, synaptic integrity, and astroglial activation across the clinical Alzheimer's disease spectrum. Issue 5 (7th March 2019) - Bos, Isabelle; Vos, Stephanie; Verhey, Frans; Scheltens, Philip; Teunissen, Charlotte; Engelborghs, Sebastiaan; Sleegers, Kristel; Frisoni, Giovanni; Blin, Olivier; Richardson, Jill C.; Bordet, Régis; Tsolaki, Magda; et al.
Abstract: Introduction: We investigated relations between amyloid‐β (Aβ) status, apolipoprotein E ( APOE ) ε4, and cognition, with cerebrospinal fluid markers of neurogranin (Ng), neurofilament light (NFL), YKL‐40, and total tau (T‐tau). Methods: We included 770 individuals with normal cognition, mild cognitive impairment, and Alzheimer's disease (AD)‐type dementia from the EMIF‐AD Multimodal Biomarker Discovery study. We tested the association of Ng, NFL, YKL‐40, and T‐tau with Aβ status (Aβ− vs. Aβ+), clinical diagnosis APOE ε4 carriership, baseline cognition, and change in cognition. Results: Ng and T‐tau distinguished between Aβ+ from Aβ− individuals in each clinical group, whereas NFL and YKL‐40 were associated with Aβ+ in nondemented individuals only. APOE ε4 carriership did not influence NFL, Ng, and YKL‐40 in Aβ+ individuals. NFL was the best predictor of cognitive decline in Aβ+ individuals across the cognitive spectrum. Discussion: Axonal degeneration, synaptic dysfunction, astroglial activation, and altered tau metabolism are involved already in preclinical AD. NFL may be a useful prognostic marker.